Malay, Chinese, and internet banking - Md. Nor, Khalil (Emerald Group Publishing Limited, 2010)
Purpose: The purpose of this paper is to focus on the impact of cultural traits on the intention to use internet banking. Drawing from the technology acceptance model and trust literature, the paper examines the influence of perceived ease of use, perceived usefulness, and trust on the intention to use internet banking among Malay and Chinese ethnic groups. Design/methodology/approach: The questionnaire was distributed to final year business students and Master of Business Administration students at four public universities in Malaysia. A separate multiple regression was employed to analyze the data for each ethnic group. Findings: For both ethnic groups, the results showed that perceived usefulness, perceived ease of use, and trust, all have significant effect on the intention to use internet banking. Further examination of the regression coefficients revealed the cultural traits that may explain the extent to which they influence factors that affect the intention to use. Research limitations/implications: Respondents of this study were students. This factor may decrease generalizability of the study because students' interest on the use of internet banking may be different from those of the general public. One research implication of this study is that there is a need to consider the role of culture in examining factors that affect behavioral intention. Practical implications: Banks need to highlight the benefits of internet banking, make internet banking easy to use, and enhance internet banking's security to improve consumers' trust. Given the fact that culture affects one's behavior, each customer group needs to be evaluated differently and the "one-size-fit-all" approach to encourage internet banking usage should be avoided. Originality/value: This paper attempts to link cultural traits that may explain the extent to which it influences factors that affect the intention to use internet banking.